A comparative study between laser hemorrhoidoplasty with digital-guided hemorrhoidal artery ligation and conventional (Milligan-Morgan) hemorrhoidectomy - Rajkumar Verma; Narendra Kumar; Vipin Mishra (Asian Journal of Medical Sciences, 2024)
Background: Hemorrhoids have a much higher incidence than rectum and colon diseases worldwide. The prevalence was estimated to be between 2.9% and 27.9% among the worldwide population, of which 4% are symptomatic. Based on the Gauss method, the highest incidence was present in patients aged between 45 and 65 years. Aims and Objectives: To compare laser hemorrhoidoplasty with digital-guided hemorrhoidal artery ligation (DGHAL) and conventional (Milligan-Morgan) open hemorrhoidectomy procedures. Materials and Methods: A prospective follow-up study was undertaken in the Department of Surgery, Maharani Laxmi Bai Medical College, Jhansi, from January 2020 to June 2021. In this comparative and prospective study, 60 patients were included, of whom 30 were treated with open surgical hemorrrhoidectomy (Milligan-Morgan) and 30 were treated with laser hemorrhoidoplasty with the DGHAL method. Results: Male patients numbered 41 and female patients numbered 19. Between laser hemorrhoidoplasty with DGHAL and the open surgical hemorrrhoidectomy (Milligan-Morgan) approach, there were significant differences in operating time, blood loss, bleeding; and early postoperative pain. In terms of early postoperative pain, there were statistically significant differences between the two groups (P<0.001). The mean operational time for laser hemorrhoidoplasty with DGHAL was 22.57±1.794 min, compared to 29.43±3.664 min for the open surgical hemorrrhoidectomy (Milligan-Morgan) method (P<0.002). Conclusion: Laser hemorrhoidoplasty with Doppler-guided hemorrhoidal artery ligation (DGHAL) is safe and effective in cases of all grades of hemorrhoids as compared to open surgical (Milligan-Morgan) hemorrhoidectomy.